Effects of foliar fungicide applications on dry bean seed quality. I. Physiological quality - Lollato, Marco Antonio; Filho, Julio Marcos (Pesquisa Agropecuaria Brasileira, 2014)
The present study was conducted at IAPAR (Teixeira Soares city, Paraná State) and at the Seed Laboratory of ESALQ/USP (Piracicaba, state of São Paulo), Brazil. Seeds from untreated bean (Phaseolus vulgaris L.) plant or plant treated during the growth phase, immediately before and immediately after flowering, with fentin, tin triphenyl acetate, chlorothalonil alone or in combination to methyl-thiophanate, were studied. The effects of fungicide applications were evaluated in the yield. The seeds were evaluated by hectoliter weight, physical purity, weight per 1.000 seeds and number of spotted and wrinkled seeds. Germination, emergence and the incidence of microorganisms on/in the seeds were carried out during one year at two-month intervals. The results indicated that the fungicide applications increased yield, volumetric weight, weight per 1.000 seeds, germination, health, and vigor of seeds. Additionally, a low level of spotted and wrinkled seeds was observed.